QIYAS VIS A VIS AD DALALAH (MENGUAK PENOLAKAN ABU MUHAMMAD TERHADAP QIYAS SEBAGAI SUMBER HUKUM ISLAM) - Mustatho, Mustatho (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
In legal Istinbath, Abu Muhammad was known as a scholar who strictly adheres to the outward texts. Therefore, he has been critical of the clergy who give the role of ratio in determining the law. In his view, Islamic law originates from Allah SWT is determined by Allah clearly in the texts of the Qur'an and Sunnah, and is practiced by consensus by Muslims. The third source of law in Islam is Ijma'. Ijma itself has to rely on the texts because there is no Ijma' without relying on the texts. So Abu Muhammad stipulates that the three sources of law above are the mains references in carrying out legal Istinbath. He rejected qiyas as the fourth source of law was the opinion of the scholars’ majority. To examine this issue, this research is literary with the substance of character research. The research method used is the content analysis method, namely analyzing the thoughts of Abu Muhammad in various existing writings. The results of the research show that to respond the various contemporary problems that arise, for which answers cannot be found explicitly in the texts, both in the Qur'an, Sunnah, and Ijma', Abu Muhammad has the method was also the fourth source of law after Ijma'. The source of law used by Abu Muhammad is known as ad Dalil. However, in further development, the concept of ad Dalil from Ibn Hazm was considered by other Ulama as a source of law or a way of Istinbath law was no different from the qiyas used by previous scholars.